Ecological Momentary Assessment of the Breakfast, Lunch, and Dinner Family Meal Environment in Racially/Ethnically Diverse and Immigrant Households - Berge, Jerica M. (J Nutr Educ Behav, 2019)
OBJECTIVE: To: (1) describe meal characteristics across breakfast, lunch, and dinner family meals in racially/ethnically diverse and immigrant/refugee households via ecological momentary assessment (EMA); (2) identify real-time meal characteristics that are associated with family meal frequency; and (3) identify qualitative themes regarding parent’s perspectives about meal characteristics and meal types that influence family meal frequency. DESIGN: Cross-sectional. SETTING: In-home visits. PARTICIPANTS: Children ages 5–7 (n=150) and their families from diverse and low income households. MAIN OUTCOME MEASURE(S): Mixed-methods. ANALYSIS: Multiple linear regression and hybrid deductive and inductive content analysis. RESULTS: Quantitative results indicated several similar meal characteristics occurring across weekday and weekend day and by meal type (e.g., parent prepared the meal, food mostly homemade, meal eaten at table) and some significant associations (p<0.05) between meal characteristics and family meal frequency (e.g., fast food for family meals). There were 8 main qualitative themes with several sub-themes that supported and expanded the quantitative findings and added depth to the interpretation of the findings. CONCLUSIONS AND IMPLICATIONS: Results identified specific meal characteristics both quantitatively and qualitatively that may inform the development of interventions to increase the frequency of family meals so that more families can benefit from the protective nature of family meals.